2016
DOI: 10.1093/cercor/bhw385
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Brain-Derived Neurotrophic Factor (proBDNF)-Mediated p75NTR Activation Promotes Depolarizing Actions of GABA and Increases Susceptibility to Epileptic Seizures

Abstract: The brain-derived neurotrophic factor (BDNF) is synthesized as a precursor, namely proBDNF, which can be processed into mature BDNF (mBDNF). Evidences suggest that proBDNF signaling through p75NTR may account for the emergence of neurological disorders. These findings support the view that the relative availability of mBDNF and proBDNF forms is an important mechanism underlying brain circuit formation and cognitive functions. Here we describe novel insights into the proBDNF/p75NTR mechanisms and function in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 110 publications
4
41
0
Order By: Relevance
“…In patients with temporal lobe epilepsy, the decrease in KCC2 expression results in depolarizing GABAergic events in a minority of subicular pyramidal cells that contribute to inter-ictal like activity (Cohen et al, 2002; Huberfeld et al, 2007). These findings are consistent with reports of KCC2 downregulation and changes in the polarity of GABAergic response in animal models of epilepsy (Huberfeld et al, 2007; Barmashenko et al, 2011; Shimizu-Okabe et al, 2011; Kourdougli et al, 2017; Riffault et al, 2018). Because both forms of BDNF regulate the expression of KCC2 (Rivera et al, 1999; Ludwig et al, 2011), the decrease observed in epileptic tissues could be due to an imbalance between mBDNF/TrkB and proBDNF/p75 NTR signaling during the first postnatal weeks causing an impaired or delayed functional maturation of GABAergic inhibition.…”
Section: Bdnf and Gaba Interplay In Epilepsysupporting
confidence: 92%
See 4 more Smart Citations
“…In patients with temporal lobe epilepsy, the decrease in KCC2 expression results in depolarizing GABAergic events in a minority of subicular pyramidal cells that contribute to inter-ictal like activity (Cohen et al, 2002; Huberfeld et al, 2007). These findings are consistent with reports of KCC2 downregulation and changes in the polarity of GABAergic response in animal models of epilepsy (Huberfeld et al, 2007; Barmashenko et al, 2011; Shimizu-Okabe et al, 2011; Kourdougli et al, 2017; Riffault et al, 2018). Because both forms of BDNF regulate the expression of KCC2 (Rivera et al, 1999; Ludwig et al, 2011), the decrease observed in epileptic tissues could be due to an imbalance between mBDNF/TrkB and proBDNF/p75 NTR signaling during the first postnatal weeks causing an impaired or delayed functional maturation of GABAergic inhibition.…”
Section: Bdnf and Gaba Interplay In Epilepsysupporting
confidence: 92%
“…The change in the regulation of GABA A Rs cell surface expression by BDNF coincides with a shift in GABA polarity (depolarization to hyperpolarization), attributed to the activity of KCC2 (Rivera et al, 1999) which is also regulated by both forms of BDNF. A recent study showed that increased proBDNF/p75 NTR signaling disrupts the developmental GABAergic sequence by maintaining a depolarizing GABA response in a KCC2-dependent manner in mature cortical neurons (Riffault et al, 2018). In developing neurons, BDNF increases KCC2 expression on the level of mRNA transcription (Aguado et al, 2003; Rivera et al, 2004; Ludwig et al, 2011).…”
Section: Probdnf Mbdnf and Gabaar Interplaymentioning
confidence: 99%
See 3 more Smart Citations